ANALISIS BONUS KOIN SHOPEE DALAM PERSPEKTIF EKONOMI SYARIAH - Al-kahfi Bunyamin, Khamal; Hayati, Imrona; Fahruddin, Achmad (At-Tawazun, Jurnal Ekonomi Syariah, 2025)
The development of digital technology has brought significant transformations in the transaction system, including the emergence of reward systems such as Shopee Coins. Shopee Coins are official virtual currencies given to Shopee application users through various promotional activities and transactions. This phenomenon is interesting to study from the perspective of sharia economics in order to assess its suitability with Islamic principles. This research is library research with a qualitative and normative approach, using primary data from the books Fiqih Muamalah by Subairi and Fiqih Muamalah Maliyah by Jaih and Hasanudin. Secondary data were also obtained from the results of interviews and analyzed to obtain descriptive conclusions. The results of the study show: first, the mechanism of obtaining Shopee Coins includes purchase transactions, participation in promotions and events, and the completion of certain missions. The system adopts gamification and loyalty to increase user engagement. Second, from the point of view of sharia economics, this system is permissible (halal) as long as it does not contain prohibited elements, such as riba, gharar (ambiguity), and maysir (gambling). Third, this system can be assessed in accordance with sharia if it is transparent and fair. Fourth, potential problems arise if there is speculation about rewards or unclear coin values. As an alternative solution, the reward system can be developed with akad ju'alah (promise of reward for a result) or tabarru' (grant) with sharia supervision, to ensure conformity with the principles of justice and ethics in Islamic muamalah.